Zarządzanie przez jakość atrakcjami turystycznymi - Wątroba, Łukasz (Quality Management of Tourism Attractions, 2005)
Tourism attractions present main power driving the tourism movement. High quality of tourism attractions causes tourists attractions: natural and made by human. Each of attraction needs another management. Other character will have natural attractions management and other made by human. However, the main idea is tourists satisfaction and simultaneously keeping these attractions for future generations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 131-136